2021
DOI: 10.1039/d1gc00818h
|View full text |Cite
|
Sign up to set email alerts
|

Efficient enzymatic hydrolysis of chitin into N-acetyl glucosamine using alkali as a recyclable pretreatment reagent

Abstract: In this study, an alkali freeze-thaw pretreatment protocol was investigated to efficiently enhance enzymatic hydrolysis of chitin into N-acetyl glucosamine (GlcNAc) at high concentrations. The optimal conditions for alkali freeze-thaw...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Along this line, the shell biorefinery concept was proposed, which targets to fractionate shells into various components and upgrade each fraction into a useful platform or end-product . Significant progress has been achieved in recent years on both upstream fractionation of shells and downstream conversions of shell components (e.g., chitin, chitosan, and their derivatives). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Along this line, the shell biorefinery concept was proposed, which targets to fractionate shells into various components and upgrade each fraction into a useful platform or end-product . Significant progress has been achieved in recent years on both upstream fractionation of shells and downstream conversions of shell components (e.g., chitin, chitosan, and their derivatives). …”
Section: Introductionmentioning
confidence: 99%
“…Mu et al reported that the hydrolysis of cellulose is sensitive to the acid density of HZSM-5, featuring a decreasing trend with an increase of the Si/Al ratio. 43 On the contrary, Onda et al indicated that zeolites with a higher Si/Al ratio (Hβ (75) and HZSM-5 (45)) are superior in glucose formation rather than Hβ (13) and H-mordenite (10) due to the comparatively higher hydrophobic properties of zeolites with higher Si/Al ratios. 44 In addition, the presence of meso-/ macropores and a larger external surface area seem to be beneficial for polysaccharide depolymerization.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Traditionally, GlcNAc is produced through chemical and enzymatic hydrolysis of crustacean shells [ 6 , 7 ]. However, there are several drawbacks to these extraction processes, such as the limitation of raw material supply and severe environmental pollution.…”
Section: Introductionmentioning
confidence: 99%
“…Methods involving the conversion of chitin to GlcNAc have been widely explored to date ( Husson et al, 2017 ; Zhang A. et al, 2021 ). In the commercial production of GlcNAc from chitin, acid hydrolysis at high temperatures is often used.…”
Section: Introductionmentioning
confidence: 99%